The Relationship between Remote Work and Job Satisfaction: The Mediating Role of Perceived Autonomy - Jamaludin, Nor Lelawati; Kamal, Sakinah Ahmad (Information Management and Business Review, 2023)
The job satisfaction of employees is one of the main keys to leading the success of an organization. It represents how you feel about your job and what you think about your job. Despite the continuous effort by the Malaysian government, the outcome of the implementation and occurrence of remote work practices towards job satisfaction in Malaysia is equivocal. Therefore, the main objective of this study is to investigate whether the impacts of remote work led to employee job satisfaction performance. This study also looks at whether perceived autonomy mediates the relationship between remote work and job satisfaction. The respondents are from one oil and gas company in Kuala Lumpur. The data were collected using an online survey among (n = 185) employees from various departments in the organization. A Statistical Package for the Social Sciences (SPSS) was developed to examine how the variables were related. Results showed that: (1) remote work has a significant relationship with job satisfaction and (2) Perceived Autonomy mediates the relationship between remote work and job satisfaction. The novelty of this research is the contribution of the present body of knowledge through the development of the adapted model of remote work-job satisfaction concerning the oil & gas industry. The findings also could guide the stakeholders and policymakers in formulating a plan and action towards the betterment of the remote work process that can elevate the job satisfaction of the organization.